An analysis of state of emergency preparedness and response of government to disaster risk management in Nigeria (2019)
Nigeria has experienced and is still experiencing varying degrees of both natural and man-made disasters with their adverse effects overtime exceeding the ability of affected societies to cope in the midst of available resources especially in the face of insurgency and terrorism. While intellectual discourses have focused on the effect and consequences of disaster, dearth of information exist on government‟s response and level of preparedness for disaster risk management especially from the analytical point of view. The paper focused on the nature and consequences of disaster, role of government in disaster risk management and problems affecting emergency preparedness and response from government. Disasters were seen to be sudden, calamitous and deadly in nature. Its types included natural disasters (e.g wild fire, floods, landslides, hurricanes, drought, damaging winds, tsunami, debris flow, hurricanes and volcanic eruption) and man-made disasters (economic collapse, terrorist attacks, chemical threat, biological threat, nuclear accidents, wars, explosions, oil and chemical spillage, fire, flood etc). Government role in disaster risk management included education, monitoring, coordination, data collation, research activities, policy making and prompt responses to prevent and control disaster at all levels. However, the hindrances included inadequacy in funding, education, coordination, research and planning. It is recommended that individual and collective effort be geared at improving education, funding and research coupled with governmental preparedness and prompt response towards the prevention and control of all forms of disaster in Nigeria.